The Consept and Principle of Multireligious Leadership - abdul amri siregar; kurniawan kurniawan (Universitas Islam Negeri Fatmawati Sukarno, 2020)
The Consept and Principle of Multireligious Leadership. Allah SWT decreed that each nation must have a leader as successor to the prophetic function. In order to keep religious doctrine, regulate the country, hold political control, make policies based on religious observance, and unite people in a singular leadership. As in the Islamic history of Prophet Muhammad SAW used the word “ra’in” which means leader. Based on a hadith, ’’kullukum ra’in, wa kullu ra’in mas-ulun ‘an ra’iyyatih” which means, “Every one of you is a leader, and every leader will be held accountable for their leadership”. In the context of Indonesia or in the context of multi-religious society, how is the guidance of Islam in the matter of leadership applied, for instance, the ban of choice non-muslim become a leader. Therefore, it must look to al-Qur’an on the issues of leadership selection. Some of these are on the surah Ali Imron verse 28, An Nisa’ verse 144, Al Maidah verse 57, At Taubah verse 23, Al Mujaadilah verse 22, An Nisa’ verse 138-139, and the others. Key word : Leadership, al-Qur’an verses, multireligious.